PEDAGOGICAL AND PSYCHOLOGICAL ROLE OF MUSIC IN CHILDREN'S DEVELOPMENT (Web of Teachers: Inderscience Research, 2023)
The article describes the influence of music on humans, its role in the development of children and on their mental performance.